2013
DOI: 10.1177/1076029613475473
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Thrombin Generation Assay With Conventional Coagulation Tests in Evaluation of Bleeding Risk in Patients With Rare Bleeding Disorders

Abstract: Based on the premise that the capacity of plasma to generate thrombin in vitro is a comprehensive and precise functional test of the clotting system, we designed a cross-sectional, single-center study involving 83 patients with rare bleeding disorders (RBDs) to compare the usefulness of the thrombin generation (TG) assay versus conventional tests including prothrombin time (PT) and activated partial thromboplastin time (aPTT) in predicting bleeding risk in patients with RBD in southern Iran. The TG parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 19 publications
2
17
0
1
Order By: Relevance
“…lagtime and ttpeak, indicating that it is mainly the amount of produced thrombin that is important for the hypercoagulability. This could be potentially important when assessing the bleeding risk, for example during invasive procedures, as prolonged lagtime has been associated with increased bleeding risk in patients with factor deficiencies [27]; however, this has not been studied in patients with liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…lagtime and ttpeak, indicating that it is mainly the amount of produced thrombin that is important for the hypercoagulability. This could be potentially important when assessing the bleeding risk, for example during invasive procedures, as prolonged lagtime has been associated with increased bleeding risk in patients with factor deficiencies [27]; however, this has not been studied in patients with liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Also, bleeding tendency was shown to become more prominent when TG decreases by more than 20% of the normal range. 11,13,17,18 Surprisingly all TG parameters except ETP showed this significant pattern in patients with mild hemophilia compared with those of healthy individuals as well. However, we should consider the small number of patients with mild hemophilia in our population (n ¼ 5).…”
Section: Discussionmentioning
confidence: 75%
“…[32][33][34] In addition, little information is available with respect to correlating BS with other parameters such as age or laboratory data. One study that used the condensed MCMDM-1VWD questionnaire showed a strong inverse correlation between BS and VWF:Ag in type 1 VWD.…”
Section: Discussionmentioning
confidence: 99%